2011
DOI: 10.1136/injuryprev-2011-040121
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic hand amputations among children in Greece: epidemiology and prevention potential

Abstract: The majority of paediatric hand and finger amputations could be prevented in Greece, particularly among preschoolers, by a single product modification, namely door closure systems, coupled with improved supervision. Paediatricians should incorporate this advice into their routine child-safety counselling. This country-specific profile supports the need for maintaining similar databases as an indispensable tool for assisting decision-making and preventing disabling and costly injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…1,13,[15][16][17] As expected, injuries from doors were the predominant the cause of hand injuries (Fig. 7).…”
Section: Discussionsupporting
confidence: 64%
“…1,13,[15][16][17] As expected, injuries from doors were the predominant the cause of hand injuries (Fig. 7).…”
Section: Discussionsupporting
confidence: 64%
“…1 Other studies have also evidenced a greater occurrence of accidents resulting from inanimate mechanical forces in the male sex. 1,5,7,10 One study undertaken in Ontario, Canada, with children aged from 6 to 11 years old, observed that the boys are significantly more involved in risky activities than are girls, 12 as the boys present more impulsive behaviors, allied with the cultural fact that the parents and guardians restrict the boys' behavior less in comparison with the girls, who are supervised more, in spite of the boys' activities and games being judged as of greater risk for accidents. [12][13] The greater incidence of accidents resulting from inanimate mechanical forces among children aged from one to four years old is corroborated by other cases.…”
Section: Discussionmentioning
confidence: 99%
“…14 In relation to the immediate physical sequelae, one study undertaken in Greece on traumatic amputations in children below 14 years of age observed that accidents with children involving doors and gates are the main causes of amputations in phalanxes, causing disabilities in individuals who are in a phase of learning and development, impairing the control and execution of fine movements. 5 It is necessary to highlight that such sequelae can be avoided through the use of 'door stopper' finger guards, are placed on the door and stop the same from closing suddenly. 5 In spite of there being few cases of inpatient treatment, one can infer through the considerable number of referrals, the need for specialized attendance and the increase in costs to the health sector, it being the case that the admissions resulting from accidental causes in the emergency services have caused a sharp increase in hospital costs.…”
Section: -20mentioning
confidence: 99%
See 2 more Smart Citations